Sistem Proteksi Portal Parkir Sepeda Motor Pada Area Parkir Universitas Dirgantara Marsekal Suryadarma - Siahaan, Rianto Parlin; Arisandi, Effendi Dodi Arisandi (Universitas Dirgantara Marsekal Suryadarma, 2025)
The Internet of Things (IoT)-based parking gate protection system was developed to enhance vehicle security in flood-prone parking areas at Universitas Dirgantara Marsekal Suryadarma. This study aims to design and evaluate an automated protection system capable of detecting water levels using the P31 float switch sensor and activating the parking gate mechanism through the NodeMCU ESP8266 microcontroller. A quantitative experimental method was applied by testing the system under various water level conditions ranging from below 100 cm to above 150 cm. Experimental results indicate that the sensor accurately detects critical flood levels between 100 and 150 cm, triggering an automatic gate-opening response within an average of 3 seconds. Furthermore, the average data transmission time from the sensor to the server is recorded at 2 seconds, demonstrating effective real-time monitoring capability. With consistent performance and rapid response, the system proves to provide additional protection against flood risks while improving the reliability of campus parking facilities.